Magnetohydrodynamics evolution of three-dimensional magnetic null in NOAA active region 11515 initiated using non-force-free field extrapolation - Kumar, Sanjay; Prasad, Avijeet; Sarkar, Ranadeep; Bhattacharyya, Ramit (Frontiers in Astronomy and Space Sciences, 2022)
Magnetohydrodynamics simulation of active region NOAA 11515 is performed to examine the initiation of the M5.6 flaring event that starts around 10:43 UT on 2 July 2012. The simulation is conducted using an extrapolated non-force-free magnetic field generated from the photospheric vector magnetogram of the active region as the initial magnetic field. The magnetic field shows the presence of a three-dimensional (3D) magnetic null with the corresponding dome overlying a filament and a low-lying magnetic flux rope, observed in 304 Å and 131 Å respectively. The simulated dynamics, triggered by the initial Lorentz force, lead to the bifurcations of the flux rope, which is similar to the observed bifurcation in the 131 Å brightenings. Additionally, the rope exhibits a rise and reconnects at the 3D null. These reconnections convert field lines of the rope into the anchored outer spine of the 3D null—explaining the occurrence of a nearby confined C-class flare. Further, the results show that the field lines of the flux rope reach the vicinity of the filament and become non-parallel to the field lines of the filament. This initiates the reconnections between the rope and the field lines of the filament—activating the filament for the eruption. This interesting interaction of the flux rope and filament seems to contribute to the onset of the M-class flare.